Taiwan Literature in the 21st Century A Critical Reader - Wu, Chia-rong.; Fan, Ming-ju. (Singapore : Springer Nature Singapore : Imprint: Springer, 2023)
This book is an anthology of research co-edited by Dr. Chia-rong Wu (University of Canterbury) and Professor Ming-ju Fan (National Chengchi University). This collection of original essays integrates and expands research on Taiwan literature because it includes both established and young writers. It not only engages with the evolving trends of literary Taiwan, but also promotes the translocal consciousness and cultural diversity of the island state and beyond. Focusing on the new directions and trends of Taiwan literature, this edited book fits into Taiwan studies, Sinophone studies, and Asian studies. .
Keywords: Oriental literature; Motion pictures; Fiction; Culture -- Study and teaching; Asian Literature; Film Studies; Fiction Literature; Cultural Studies